1992
DOI: 10.1164/ajrccm/146.5_pt_1.1177
|View full text |Cite
|
Sign up to set email alerts
|

Effects on the Isolated Human Bronchus of SR 48968, a Potent and Selective Nonpeptide Antagonist of the Neurokinin A (NK2) Receptors

Abstract: Tachykinins produce concentration-dependent contraction of the human isolated bronchus by stimulation of receptors that belong to the NK2 type. The aim of this study was to investigate the inhibitory effects of a new, potent, and selective nonpeptide antagonist of the neurokinin A (NKA) (NK2) receptors, SR 48968 [(S)-N-methyl-N-[4-acetylamino-4-phenylpiperidino-2-(3,4-dichlorophenyl) butyl]benzamide] on human isolated airways. Our experiments were performed on human isolated bronchi obtained from patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
64
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 13 publications
4
64
1
Order By: Relevance
“…Classically, the expression of NK 1 R and NK 2 R has been described in both the nervous system and peripheral target organs, including human airways, whereas the expression of NK 3 R was believed to be more limited to the central and peripheral nervous system (31,34). Furthermore, it has traditionally been thought that only the NK 2 R mediated direct contraction of airway smooth muscle, especially in human airways (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Classically, the expression of NK 1 R and NK 2 R has been described in both the nervous system and peripheral target organs, including human airways, whereas the expression of NK 3 R was believed to be more limited to the central and peripheral nervous system (31,34). Furthermore, it has traditionally been thought that only the NK 2 R mediated direct contraction of airway smooth muscle, especially in human airways (3).…”
mentioning
confidence: 99%
“…Furthermore, it has traditionally been thought that only the NK 2 R mediated direct contraction of airway smooth muscle, especially in human airways (3). However, recently it was reported that in smalldiameter human bronchi, tachykinins also cause contraction via NK 1 R stimulation (4).…”
mentioning
confidence: 99%
“…Although NK 2 receptors play a prominent role in the bronchoconstrictor effect of tachykinins [7], NK 1 receptors can also mediate the bronchoconstriction, especially due to their presence in the small-and medium-sized bronchi. Immune histochemistry has demonstrated the presence of both NK 1 and NK 2 receptors in the smooth muscle of the human lung.…”
Section: Drug Safetymentioning
confidence: 99%
“…Of all these effects, bronchoconstriction is the most studied effect [5]. Asthmatic [6] patients are more sensitive to the bronchoconstrictor effect of substance P and NKA [7][8][9]. Studies on isolated human airways have shown that tachykinin-induced bronchoconstriction is mainly caused by activation of the tachykinin NK 2 receptor [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation